2022
DOI: 10.3390/rs15010022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Economic Recovery in Hebei Province, China, under the COVID-19 Pandemic Using Nighttime Light Data

Abstract: The COVID-19 pandemic has presented unprecedented disruptions to human society worldwide since late 2019, and lockdown policies in response to the pandemic have directly and drastically decreased human socioeconomic activities. To quantify and assess the extent of the pandemic’s impact on the economy of Hebei Province, China, nighttime light (NTL) data, vegetation information, and provincial quarterly gross domestic product (GDP) data were jointly utilized to estimate the quarterly GDP for prefecture-level cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…If the slopes of the post-earthquake SVANUI trajectories (k1 and k3) are greater than the slope of the pre-earthquake SVANUI trajectory (k0), it is reasonable to assume that the regional economy will experience a rebound; If the slope of the post-earthquake SVANUI trajectory (k2) is first greater than k0 and then less than or equal to k0, it can be concluded that the regional economy will not recover within a specified period. Similarly, if the slope of the postearthquake SVANUI trajectory (k4) is less than 0, it can be inferred that the regional economy is in recession and is not expected to recover in the short term [60].…”
Section: Assessment Methods Of Eonomic Recovery From Affected Areamentioning
confidence: 99%
See 1 more Smart Citation
“…If the slopes of the post-earthquake SVANUI trajectories (k1 and k3) are greater than the slope of the pre-earthquake SVANUI trajectory (k0), it is reasonable to assume that the regional economy will experience a rebound; If the slope of the post-earthquake SVANUI trajectory (k2) is first greater than k0 and then less than or equal to k0, it can be concluded that the regional economy will not recover within a specified period. Similarly, if the slope of the postearthquake SVANUI trajectory (k4) is less than 0, it can be inferred that the regional economy is in recession and is not expected to recover in the short term [60].…”
Section: Assessment Methods Of Eonomic Recovery From Affected Areamentioning
confidence: 99%
“…The annual NTL data were also adopted to develop a resilience model for disaster recovery after the 2008 Wenchuan earthquake and to analyze potential factors that influence the economic recovery process [28,29]. Li et al [30] used monthly NTL data to estimate the quarterly gross domestic product (GDP) at the prefecture and county levels in Hebei Province, China. In addition, they designed an economic recovery intensity model to assess the extent of economic recovery in Hebei Province during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its reliance only on endogenous variable and not requiring assistance from other exogenous variables, it can be effectively combined with NTL data. The ARIMA model has not been widely combined with NTL data, so it has only been applied to predict the GDP of various provinces in China [ 52 , 53 ]. In other fields, the combination of the ARIMA model and NTL data still holds great potential for application, so we are applying it to predict human activities along border areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data were collected using questionnaires that assessed the happiness of farmers, farmers' adoption of AGP, mediation variables, and control variables. As the COVID-19 pandemic has been going on in China for more than three years [84], the current study may have been limited in terms of the depth and breadth of data. Panel data were not used for the study.…”
Section: Variablesmentioning
confidence: 99%